Tekirdağ İlindeki Tarımsal İşletmelerdeki Pülverizatörlerin Durumu ve Sorunları Üzerine Bir Araştırma - İlker H. Çelen; Cihan Demir (Journal of Agricultural Sciences)
Determination of mechanization level according to plant protection machines carried out on mainly aimed in this research. Problems, maintenance, service and buying cost of the machines were also found out by randomize survey on farms in Tekirdag. The survey included 20 questions. This survey was 718 farmers in villages determined beforehand. Some problems were also recorded except the questions in the survey. The smallest land was determined with 20 da and the largest with 4000 da according to the result. The rate of enterprises which has 101-250 da land was 47.15%. 501 Tractors, 621 cultivators, 519 sprayers were determined according to survey. The rate of sprayer/tractor was found as 1.036. Ages of the sprayers were mostly under 10 years (41 %). Ages of others machines were determined as fewer than 5 years with 35% and older than 21 years with 3%. By observation of sprayer; 79% of them were found to be well and 28% were found to be nozzle clogged. 11% of farmers stated that they always controlled nozzles and when they found some problems they changed with the new ones. In this research, it was also determined that 73% farmers cleaned the machines after each use. 59% maintained and serviced their machines in their own workshop.